2016
DOI: 10.1002/lary.26364
|View full text |Cite
|
Sign up to set email alerts
|

Lower airway disease and pituitary surgery: Is there an association with postoperative cerebrospinal fluid leak?

Abstract: 2c. Laryngoscope, 127:1543-1550, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The increased intrathoracic pressure leading to a decreased blood ow of the jugular vein resulting in an increased intracranial pressure may cause herniation of the repaired material from the sellar base and CSF leakage. Two other studies 11,12 had proven the mechanism of an increased intracranial pressure playing an important role in the occurrence of postoperative CSF leakage or a spontaneous CSF leakage. Hanba et al 12 discovered that patients with asthma are more likely to have CSF leakage than patients without asthma after transnasal surgery; further, the rate of postoperative CSF leakage in these two groups was 4.7% and 2.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased intrathoracic pressure leading to a decreased blood ow of the jugular vein resulting in an increased intracranial pressure may cause herniation of the repaired material from the sellar base and CSF leakage. Two other studies 11,12 had proven the mechanism of an increased intracranial pressure playing an important role in the occurrence of postoperative CSF leakage or a spontaneous CSF leakage. Hanba et al 12 discovered that patients with asthma are more likely to have CSF leakage than patients without asthma after transnasal surgery; further, the rate of postoperative CSF leakage in these two groups was 4.7% and 2.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies 11,12 had proven the mechanism of an increased intracranial pressure playing an important role in the occurrence of postoperative CSF leakage or a spontaneous CSF leakage. Hanba et al 12 discovered that patients with asthma are more likely to have CSF leakage than patients without asthma after transnasal surgery; further, the rate of postoperative CSF leakage in these two groups was 4.7% and 2.7%, respectively. Fleischman et al 11 found that patients with obstructive sleep apnea are more likely to develop a spontaneous CSF leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The increased intrathoracic pressure leading to decreased blood flow in the jugular vein, resulting in increased intracranial pressure, may cause herniation of the repaired material from the sellar base and thus, CSF leakage. Two other studies [ 11 , 12 ] have shown that an increased intracranial pressure plays an important role in the occurrence of postoperative CSF leakage or spontaneous CSF leakage. Hanba et al [ 12 ] discovered that patients with asthma are more likely to have CSF leakage than patients without asthma after transnasal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies [ 11 , 12 ] have shown that an increased intracranial pressure plays an important role in the occurrence of postoperative CSF leakage or spontaneous CSF leakage. Hanba et al [ 12 ] discovered that patients with asthma are more likely to have CSF leakage than patients without asthma after transnasal surgery. Furthermore, the rates of postoperative CSF leakage in these two groups were 4.7% and 2.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%